2005
DOI: 10.1007/s00384-004-0727-9
|View full text |Cite
|
Sign up to set email alerts
|

Effective antitumour mono- and combination therapy by gene delivery of angiostatin-like molecule and interleukin-12 in a murine hepatoma model

Abstract: In conclusion, both mono- and combination therapy of K1-3 and IL-12 significantly inhibited tumour progression in this experimental tumour model. The co-administration of both compounds did not result in additive antitumour effects. We hypothesise that the lack of additive antitumour effects of the combination treatment might be attributed to partially counteracting antitumour effects and further studies are needed to illustrate the interference of tumour angiogenesis and tumour inflammation in this tumour mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A safer approach is based on the use of gene therapy vectors that are able to express IL-12 at the local tumor site. Intratumoral administration of firstgeneration adenoviral vectors expressing IL-12 has shown strong antitumoral effects in preclinical models of primary and metastatic HCCs (Caruso et al, 1996;Andrews et al, 2000;Barajas et al, 2001;Schmitz et al, 2005;Waehler et al, 2005). Moreover, a phase I clinical trial based on this strategy showed low toxicity and tumor infiltration by effector immune cells, resulting in one objective tumor remission in a patient with advanced HCC (Sangro et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…A safer approach is based on the use of gene therapy vectors that are able to express IL-12 at the local tumor site. Intratumoral administration of firstgeneration adenoviral vectors expressing IL-12 has shown strong antitumoral effects in preclinical models of primary and metastatic HCCs (Caruso et al, 1996;Andrews et al, 2000;Barajas et al, 2001;Schmitz et al, 2005;Waehler et al, 2005). Moreover, a phase I clinical trial based on this strategy showed low toxicity and tumor infiltration by effector immune cells, resulting in one objective tumor remission in a patient with advanced HCC (Sangro et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…No spontaneous tumour elimination was observed in this model. 12 In this intention-to-treat study, angiostatic vector activity was associated with an overall reduction in tumour growth for both constructs, AdPlgK1-4 and AdPlgK1-5. Compared with control AdLacZ, tumour growth was significantly reduced by 38% for AdPlgK1-4 and 67% for AdPlgK1-5 in the surviving animals at day 12, with a treatment benefit of another 38% for AdPlgK1-5 compared with AdPlgK1-4 (p.0.05).…”
Section: Local Treatmentmentioning
confidence: 76%
“…[3][4][5][6][7][8][9] Consecutively, a spectrum of angiostatic treatments has been tested to be effective in HCC, embracing-among others-anti-VEGF treatments, endostatin and angiostatin. [5][6][7][8][9][10][11][12][13][14][15] Plasminogen derivates such as angiostatin are well-known antiangiogenic factors. Angiostatin was first described in 1994: O'Reilly et al 16 showed that application of angiostatin resulted in a marked inhibition of tumour growth in a murine Lewis Lung Cancer model.…”
mentioning
confidence: 99%
“…It was found that injection of rAAV-K1-3 or rAAV-IL-12 into tumor nodules resulted in a significant dose-dependent reduction in tumor growth, while the survival rate was significantly improved in the IL-12 treated mice, but not in the K1-3 treated mice. Combined therapy of these genomedicines, however, did not further improve antitumor efficacy compared with the monotherapy [83].…”
Section: Anti-angiogenesis Gene Therapymentioning
confidence: 79%